Resurrection: a reflection from art, thought, science and law - Garcés Garcés, Hugo Alexander (2023)
The legal world and the real world consider some facts relevant, qualifying them as legal categories, death being one of them. In both worlds the fact of death is assumed from different approaches, always as the end of life and the beginning of something else. In this essay, by means of a periodic review, the fact of death as a finite category is approached, analyzing a hypothetical case of resurrection. Death and resurrection are described from different perspectives, with the support of examples of how they have been approached by mythology, cinema, science and literature. Finally, some reflections are made regarding the legal effects that resurrection could generate, considering in any case, the time variable, that is, if the period of death were to beprolonged.